1994
DOI: 10.1002/1097-4679(199411)50:6<906::aid-jclp2270500615>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and anger in interpersonal violence offenders

Abstract: The current literature on psychopathology and anger suggests that both contribute to interpersonal violence. The present study examined psychopathology and anger expression with two objectives to confirm previous distinctions of personality type among abusive individuals and to examine the relation between these types and anger. Cluster analysis was conducted with data gathered from 40 subjects. Results suggested confirmation of four clusters of interpersonal violence offenders. Furthermore, the most pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 6 publications
(5 reference statements)
1
23
1
Order By: Relevance
“…This is especially important for those victims who wish not to separate from their violent spouse and for families who show both spouse abuse and child abuse. 2) Greene, Coles & Johnson (1994) 3) Gottman et al (1995) 4) Hamberger et al (1996) 5) Rothschild et al (1997) 6) Greene, Lynch & Decker (1997) HR = heart rate: APD = antisocial personality disorder: BPO = borderline personality organisation: DNV = distressed nonviolent:…..NDNV = non distressed non violent: MCMI-= Millon Clinical Multiaxial Inventory (Millon 1983), MCMI-II (Millon 1987), MCMI-III (Millon 1994) MMPI = Minesota Mulktiphasiac Personality Inventory: (Graham, 1987;Hathaway & Mckinley, 1967) STAXI = State-Trait Anxiety Expression Inventory (Spielberger 1988) BDI = Beck Depression Inventory (Beck et al 1961) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is especially important for those victims who wish not to separate from their violent spouse and for families who show both spouse abuse and child abuse. 2) Greene, Coles & Johnson (1994) 3) Gottman et al (1995) 4) Hamberger et al (1996) 5) Rothschild et al (1997) 6) Greene, Lynch & Decker (1997) HR = heart rate: APD = antisocial personality disorder: BPO = borderline personality organisation: DNV = distressed nonviolent:…..NDNV = non distressed non violent: MCMI-= Millon Clinical Multiaxial Inventory (Millon 1983), MCMI-II (Millon 1987), MCMI-III (Millon 1994) MMPI = Minesota Mulktiphasiac Personality Inventory: (Graham, 1987;Hathaway & Mckinley, 1967) STAXI = State-Trait Anxiety Expression Inventory (Spielberger 1988) BDI = Beck Depression Inventory (Beck et al 1961) …”
Section: Resultsmentioning
confidence: 99%
“…There is no reason to suggest that all domestic violent men are alike, indeed Huss et al (2000) asserts that researchers have increasingly concluded that there is not a unitary profile for violent men in domestic settings. Recent research has demonstrated that spouse abusers are not a homogenous group, efforts to conceptualise the aetiology of domestic violence have resulted in the production of typologies of domestic violent men (Holtzworth-Munroe and Stuart 1994;Hamberger 1996;White and Gondolf 2000;Greene, Coles and Johnson 1994;Monson and Langhinnchsen-Rohling 1998). The categorisation of spouse abusers into subgroups will increase the understanding of the domain.…”
Section: Table 1 About Herementioning
confidence: 99%
See 2 more Smart Citations
“…Recent theoretical and empirical developments in both the USA and the UK have suggested that spouse abusers are not a homogeneous group (Dixon & Browne, 2003;Gilchrist et al, 2003a,b;Grann & Wedin, 2002;Greene, Coles, & Johnson, 1994;Holtzworth-Munroe, 2000;Holtzworth-Munroe & Stuart, 1994;Johnson, 1995;Tweed & Dutton, 1998). While the typologies have varied in identifying two, three, or four subgroups, one dimension which is common to all is the distinction between instrumental, planned, or anti-social violence and expressive, impulsive, or angry violence.…”
Section: Angermentioning
confidence: 99%